Holding Polluting Countries to Account for Climate Change: Is "Loss and Damage" Up to the Task?. Issue 1 (28th November 2016) - Johnson, Craig A.
Abstract: Formally established by the Conference of the Parties to the UN Framework Convention on Climate Change in 2013, the Loss and Damage Mechanism represents what is for many an important effort on the part of developing countries (including China and the G77) to hold polluting countries to account for past and potential harms incurred as a result of climate change. This paper explores the viability of using the Mechanism as a means of holding polluting countries to account for the provisions outlined in the Framework Convention. In reviewing the history and recent policy within the UNFCCC, the paper makes the case that demands for greater accountability through the Loss and Damage Mechanism have been frustrated by a lack of consensus about the rights of poor countries to pursue carbon‐intensive development pathways, the obligations of current and future generations to the actions and decisions of their forebears, and the obligations of national governments to their own citizens and the UNFCCC. Instead of assigning responsibility for past and future losses and damages, the Mechanism has gravitated toward a more technocratic/bureaucratic exercise aimed at collecting data, enhancing knowledge, and making policy recommendations.